Paraoksonaz-1 Enziminin Bazı Kinetik Özelliklerinin İncelenmesi ve Ghrelin Hormonu ile İlişkisi - Aşkın, Uğur; Karataş, Fikret; Türköz, Yusuf; Aydın, Süleyman (İnönü Üniversitesi, 2012)
Bu çalışmada, sığır karaciğerinden saflaştırılan ve metabolizma için büyük öneme sahip olan Paraoksonaz-1 E.C. 3.1.1.2. ve E.C. 3.1.8.1. enziminin bazı kinetik özellikleri ile ghrelin hormonu arasındaki ilişki araştırıldı. Paraoksonaz-1 enziminin pH:7.1 ve 37 ºC’de optimum aktivite gösterdiği saptandı. Substrat olarak fenil asetat kullanıldığında Km değeri 0.074 + 0.002 mM ve Vmax değeri 36.42 U/mg olarak hesaplandı. Paraoksonaz-1 enziminin aktif ghrelin hormonuna etki ettiği ve aktif ghrelin hormonunu 20 dakika sonunda % 9.5 oranında inaktif ghreline dönüştürdüğü tespit edildi

In this study, some of the kinetic features of paraoxonase-1 E.C. 3.1.1.2. and E.C. 3.1.8.1. that is purified from bovine liver and has major importance for metabolism and, the relationship between paraoxonase-1 and ghrelin hormone has been investigated. It is seen that paraoxonase-1 displays optimum activity at pH: 7. 1 and 37 ºC. When phenyl acetate is used as a substrate, it is calculated that Km value was 0.074 + 0.002 mM and Vmax value was 36.42 U/mg. It is determined that paraoxonase-1 interacts with the active ghrelin and converts it into the inactive ghreline at the end of 20 minutes. The converting rate was found as 9.5 %
Investigation of the Some Kinetic Features of Paraoxonase-1 Enzyme and Its Relationship with Ghreline Hormone